Difficult Decisions in Vascular Surgery : An Evidence-Based Approach - Skelly, Christopher L.; Milner, Ross (Springer International Publishing : Imprint: Springer, 2017)
This book looks at specific vascular surgery questions that have arisen and where careful analysis is given according to the level of supporting evidence available. As new technology is introduced to treat the cardiovascular system, alternative therapies begin to challenge and also complement traditional vascular surgery. All chapters contain the PICO table to summarise specific characteristics relative to the questions posed in each chapter. Difficult Decisions in Vascular Surgery- An Evidence-Based Approach is a current and timely reference source for practicing surgeons, surgeons in training, and educators, that describes the recommended ideal approach, rather than customary care, in selected clinical situations.
Keywords: Medicine.; Oncology.; Cardiac surgery.; Vascular surgery.; elektronické knihy; electronic books